Evaluation of movement and physiological demands of Rugby League referees using Global Positioning Systems tracking - O'Hara, J. P.; Brightmore, A.; Till, K.; Mitchell, I.; Cummings, S.; Cooke, C. B. (International Journal of Sports Medicine, 2013)
The use of global positioning systems (GPS) technology within referees of any sport is limited. Therefore, the purpose of the current study was to evaluate the movement and physiological demands of professional rugby league referees using GPS tracking analysis. Time-motion analysis was undertaken on 8 referees using 5-Hz GPS devices and heart rate monitors throughout a series of Super League matches. 44 data sets were obtained with results identifying similar total distance covered between first and second half periods with a significant (P=0.004) reduction in the number of high velocity efforts performed between 5.51-7.0 m.s-1 (1st=21±8, 2nd=18±8). Mean distance covered from greatest to least distance, was 3 717±432 m, 3 009±402 m, 1 411±231 m, 395±133 m and 120±97 m for the following 5 absolute velocity classifications, respectively; 0.51-2.0 m.s-1; 2.1-4.0 m.s-1: 4.01-5.5 m.s-1; 5.51-7.0 m.s-1; <7.01 m.s-1. Heart rate was significantly (P<0.001) greater in the first (85.5±3.4% maxHR) compared to the second (82.9±3.8% maxHR) half. This highlights the intermittent nature of rugby league refereeing, consisting of low velocity activity interspersed with high velocity efforts and frequent changes of velocity. Training should incorporate interval training interspersing high velocity efforts of varying distances with low velocity activity while trying to achieve average heart rates of ~ 84% maxHR to replicate the physiological demands.